The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.25259/jgoh_3_2021
|View full text |Cite
|
Sign up to set email alerts
|

Patients awareness, perception, and willingness toward dental treatment during COVID-19 pandemic in India

Abstract: Objectives: COVID-19 has badly affected the global economy, also affecting the health-care sector with a major effect on dentistry. It is important to understand the reason behind it from patient’s perspective, by knowing their awareness, perception, and willingness toward dental treatment during COVID-19 times. This might help the dentist to increase patient inflow. Materials and Methods: A cross-sectional study was conducted using an online survey. A validated questionnaire was circulated to participants b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Dentists have a high risk of being infected with COVID-19 because they are exposed to droplets directly when working with patients (Fallahi et al, 2020;Spagnuolo et al, 2020;Umeh et al, 2021). The patient's awareness of contracting an infection during the handling procedure is one of the considerations in carrying out dental care in health services (Ahmed et al, 2020;Kokane et al, 2022). One study reported that patients who thought they could be infected with COVID-19 during dental treatment and were likely to be infected by other patients at the treatment site had higher anxiety scores than those who thought otherwise (Karagözoğlu & Parlar, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Dentists have a high risk of being infected with COVID-19 because they are exposed to droplets directly when working with patients (Fallahi et al, 2020;Spagnuolo et al, 2020;Umeh et al, 2021). The patient's awareness of contracting an infection during the handling procedure is one of the considerations in carrying out dental care in health services (Ahmed et al, 2020;Kokane et al, 2022). One study reported that patients who thought they could be infected with COVID-19 during dental treatment and were likely to be infected by other patients at the treatment site had higher anxiety scores than those who thought otherwise (Karagözoğlu & Parlar, 2021).…”
Section: Resultsmentioning
confidence: 99%